THE INFLUENCE OF LIVE STREAMING FEATURES ON PURCHASE INTENTION FROM THE CONSUMER FUNCTIONAL EXPERIENCE AND EMOTIONAL CONTAGION PERSPECTIVE - Tiara Oktapiani; Mochamad Yudha Febrianta (SEAN Institute, 2023)
The massive growth in popularity of TikTok in Indonesia over the past few years has had a huge impact on economic growth in Indonesia. TikTok facilitates its users to reach a wider audience by utilizing the live broadcast feature, thus increasing their chances of attracting new customers. The purpose of this study is to investigate the factors that influence consumer purchase intentions on the live streaming platform, especially from the functional consumer experience and emotional contagion perspective. This study was studied using a quantitative descriptive methodology with data collection techniques in the form of a questionnaire-based survey and literature study. Then, the collected data were then analysed using a partial least square with the statistical software SmartPLS.3.2.9. The results indicated that Erigo Store live streaming features in interactivity and convenience has a positive significant influence on the consumer functional experience, pleasant emotion, emotional trust, and purchase intention. Therefore, interactivity has no positive significant influence on purchase intention. Also, at the low structural level, the consumer's functional experience, pleasant emotion, and emotional trust have a positive significant influence on mediating the link between the Erigo Store live streamers' interactivity and the live streaming convenience in relation to the intention to make a purchase.